Penentuan Status Mutu Air Sungai Wrati Pasuruan Jawa Timur dengan Indeks Kualitas Air - Abdillah Akmal Karami; Harmin Sulistiyaning Titah (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The Wrati River is located in PasuruanRegency. This river crosses three sub-districts and six sub-districts, with a total distance of 13.6 kilometers. The subdistrict through which this river passes has land use for household, agricultural, and industrial purposes. These activities hurt rivers, causing pollution and decreasing water quality. Determining water quality status is very important to understand the suitability of river water for various purposes. Understanding water quality can be fundamental information for managing and preventing river pollution. The pollutant index approach used in this research refers to the guidelines in the Decree of the Minister of the Environment Number 115 of 2003. The research results show that the water quality of the Wrati River from upstream to downstream is included in the lightly polluted category at each sampling point, with an index value of 4.94. The main factor causing light pollution in Wrati River water is the excessive phosphate content and other parameters that exceed the specified quality standards. Based on the findings of this research, waste management efforts need to be made to improve the quality of this river water